Order 5 matrix determinant calculation with a method similar to Sarrus (Research, Society and Development, 2023)
This research aimed to investigate the possibility of calculating the determinant of matrices of order 5 through a new method similar to the one developed by Sarrus, obtained through the extension of Sarrus' rule and procedures characteristic of Gbemi's method. The methodology consisted of an exploratory research, where first, definitions, theorems and the new method were known and based on apt bibliography and related to the theme, and then applied the method in the calculation of the determinant. The results showed that the tool was able to correctly calculate the determinant of a generic matrix of order 5, and later, the technique was applied in some non-generic matrices, with their respective particularities, that is, in real problems, and it was also achieved arrive at the correct answer, concluding that the technique is efficient and capable of performing this computation in matrices of such order.